The Dynamics of Higher Education Development in East Asia Asian Cultural Heritage, Western Dominance, Economic Development, and Globalization - Neubauer, Deane; Shin, Jung Cheol; Hawkins, John N.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This book examines four theses regarding Asian higher education and development: interplay between cultural traditions, economic development, globalization, and the evolution of the'hybrid' university. Top scholars evaluate these hypotheses and determine the elements shaping the history and present circumstances of Asia-Pacific higher education.
Keywords: Science; Science; Science, general